Perancangan Arsitektur Enterprise Menggunakan Togaf Framework (Studi Kasus : Cv. Agung Lestari) - Andreas Perdana; Suhendro Yusuf (Sienna, 2020)
CV. Agung Lestari is a company engaged in services of new vehicle’s documents. The company activities are using Information System (IS) and Information Technology (IT) and already have an application that used in Administration Division. However, in the absence of data integration and connection to information system between divisions. Unintegrated data allows for data redundancy, error, lack of data accuracy, and less efficient. Required a framework in planning, designing, and managing infrastructure called Enterprise Architecture(EA). The design in the form of System Administration, Finance Management System, Human Resource and Accounting. Data any information system is already integrated.